Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

F(x) = 2x^3 + 5x^2 -6x-7 g(x) = 2x-3 find (f - g) (x)

Fx 2x3 5x2 6x7 Gx 2x3 Find F G X class=

Sagot :

Given:

The function are:

[tex]f(x)=2x^3+5x^2-6x-7[/tex]

[tex]g(x)=2x-3[/tex]

To find:

The function (f-g)(x).

Solution:

We have,

[tex]f(x)=2x^3+5x^2-6x-7[/tex]

[tex]g(x)=2x-3[/tex]

We need find (f-g)(x).

[tex](f-g)(x)=f(x)-g(x)[/tex]

[tex](f-g)(x)=2x^3+5x^2-6x-7-(2x-3)[/tex]

[tex](f-g)(x)=2x^3+5x^2-6x-7-2x+3[/tex]

On combining like terms, we get

[tex](f-g)(x)=2x^3+5x^2+(-6x-2x)+(-7+3)[/tex]

[tex](f-g)(x)=2x^3+5x^2-8x-4[/tex]

Therefore, the correct option is B.